Het museumboek : hoogtepunten uit de verzameling. - Huvenne, Paul; Maréchal, Els; Devisscher, Hans; Koninklijk Museum voor Schone Kunsten, Antwerpen (Antwerpen : KMSKA (Koninklijk Museum voor Schone Kunsten Antwerpen) Antwerpen, 2003)
Alechinsky, Pierre ; Appel, Karel ; Van Beers, Jan ; van den Berghe, Frits ; Breitner, George Hendrik ; Brusselmans, Jean ; Claus, Emile ; D'Haese, Roel ; Delvaux, Paul ; Dupon, Josué ; Ensor, James ; Frederic, Léon ; Grosz, George ; Laermans, Eugene ; Lamorinière, François ; Magritte, René ; Mellery, Xavier ; Meunier, Constantin ; Minne, George ; Modigliani, Amedeo ; Mortier, Antoine ; Peeters, Jozef ; Permeke, Constant ; Raveel, Roger ; Rodin, Auguste ; Van Rysselberghe, Theo ; Schmalzigaug, Jules ; Servaes, Albert ; Servranckx, Victor ; De Smet, Gustave ; Smits, Jakob ; Spilliaert, Léon ; Stobbaerts, Jan ; Tissot, James Jacques Joseph ; Uecker, Günther ; de Velde, Henri Van ; de Woestyne, Gustave Van ; Wouters, Rik ; Zadkine, Ossip
Nederlands
boek